Ecology and morphology of household ant, Paratrechina longicornis (LATREILLE, 1802) In South Eastern of Johor - Mohd Yusof, Shabanun Salwa (2012)
Paratrechina longicornis is an invasive ant which may act as a predator upon pest species in plantations and agriculture farms. In spite of that, this cosmopolitan ant species is also a pest in houses (Fox et al, 2007) and was discovered as a mechanical camer of pathogenic microorganisms in hospital environment in Brazil (Moreira et al., 2005). The objectives of this study are to determine the occurrence, morphology and behavioural pattern activity of P. longicornis in built area and natural environment of Johor, the variation in the nesting preferences of P. longicornis occurring in wooden house and concrete houses and to compare the behaviowal activity patterns and morphology of P. longicornis occurring in built area and natural environment of Johor. Three sites were selected, Endau-Rompin National Park, Kahang and Kg Peta as the natural environment, built and rural area respectively. No P.longicornis was found in the undisturbed area of Endau-Rompin National Park, 654 and 2547 individuals of P. longicornis were collected in Kg Peta and Kahang through manual collection. All individuals of P. longicornis observed all areas were black in color. Sometimes, when they were exposed to the sun, it seems to be seen as darkish brown and shiny. Variability occurs and may be dimorphic in size of the workers. The sizes of minor (2.500mm * 0.316) and major (3.269mm + 0.274) workers of P. longicornis in build area are larger than the ants found in the rural area (2.303rnm + 0.246 and 3.118mm 5 0.224 respectively. P. longicornis were only found nesting in two of the wooden houses and four concrete houses fiom 10 houses chosen in Kg Peta. From the observation made to see the behavioral pattern of activities of P. longicornis, in Kg. Peta, P. longicornis has their own nesting preferences; 1) safe and protected fiom weather and macroclimate such as direct sunrays, rain and wind, 2) has good thermoregulato~yt o heat and humidity (depends on the host material, 3) nearest to the wide variety of food sources, 4) enough space for their nest establishment and reproduction and 5) nest must be ecologically secure. P. longicornis were abundant and highly adaptable to concrete house as the nesting sites were discovered mostly in the concrete houses rather than the wooden house. The peak hour of the activities of P. longicornis observed in Kg Peta was during night time. In Kahang (built area), activity pattern seemed to contrast to that of the Kg Peta (ma1 area). The activities of P. longicornis in were found to be affected by humidity, temperature and rain. It was observed that the activities of P. longicornis are closely related to the human activities that was the active period of the ant is during day time. This study provides up to date biological information of P. longicornis as a pest species in Malaysia and to be a good biological indicator to disturbance as it is only can be found in such area.